Political Implications of Criminal Law in Efforts to Protect River from Pollution - Ismaidar; Prabowo, Deny (Universitas Muhammadiyah Palu, 2024)
This study aims to discuss the legal regulation of river environmental protection, as well as comprehensively examine the legal policies (penal and non-penal) of river protection from pollution. The research method used is normative legal research, namely research referring to legal norms in laws and regulations, libraries, and norms in society. The type of research used qualitative research is carried out by examining literature materials in the field of law and legislation related to the problem under study. The results of this study show that the legal regulation of river environmental protection is regulated in several regulations, including Law No. 32 of 2009 concerning Environmental Protection and Management, Law No. 17 of 2019 concerning Water Resources, PP No. 38 of 2011 concerning Rivers, and PP No. 37 the Year 2012 on Watershed Management. The penal policy includes normative legal arrangements contained in laws and government regulations on river environmental protection, imposing criminal sanctions to give the effect of looting. Non-penal policies are reforestation of the river environment, revitalization of industrial estates, increasing public awareness, sustainable resource management, and empowerment of green technology (environmentally friendly).